Comparative analysis of magnetically activated cell sorting and ultracentrifugation methods for exosome isolation - Eda Ciftci; Naz Bozbeyoglu; Ihsan Gursel; Feza Korkusuz; Feray Bakan Misirlioglu; Petek Korkusuz (PLoS ONE, 2023)
Mesenchymal stem cell-derived exosomes regulate cell migration, proliferation, differentiation, and synthesis of the extracellular matrix, giving great potential for the treatment of different diseases. The ultracentrifugation method is the gold standard method for exosome isolation due to the simple protocol, and high yield, but presents low purity and requires specialized equipment. Amelioration of technical optimization is required for quick and reliable confinement of exosomes to translate them to the clinic as cell therapeutics In this study, we hypothesized that magnetically activated cell sorting may provide, an effective, reliable, and rapid tool for exosome isolation when compared to ultracentrifugation. We, therefore, aimed to compare the efficiency of magnetically activated cell sorting and ultracentrifugation for human mesenchymal stem cell-derived exosome isolation from culture media by protein quantification, surface biomarker, size, number, and morphological analysis. Magnetically activated cell sorting provided a higher purity and amount of exosomes that carry visible magnetic beads when compared to ultracentrifugation. The particle number of the magnetically activated cell sorting group was higher than the ultracentrifugation. In conclusion, magnetically activated cell sorting presents a quick, and reliable method to collect and present human mesenchymal stem cell exosomes to clinics at high purity for potential cellular therapeutic approaches. The novel isolation and purification method may be extended to different clinical protocols using different autogenic or allogeneic cell sources.